The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1042/cs20160064
|View full text |Cite
|
Sign up to set email alerts
|

Local inhibition of elastase reduces EMILIN1 cleavage reactivating lymphatic vessel function in a mouse lymphoedema model

Abstract: Lymphatic vasculature critically depends on the connections of lymphatic endothelial cells with the extracellular matrix (ECM), which are mediated by anchoring filaments (AFs). The ECM protein EMILIN1 is a component of AFs and is involved in the regulation of lymphatic vessel functions: accordingly, Emilin1−/− mice display lymphatic vascular morphological alterations, leading to functional defects such as mild lymphoedema, lymph leakage and compromised lymph drainage. In the present study, using a mouse post-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Proteases secreted by infiltrated neutrophils are able to fragment EMILIN1 in lymphoedematous tissues. This degradation is abolished by the NE specific inhibitor sivelestat but not by the MMPs broad-spectrum inhibitor GM600128. In the present study we demonstrated that the functional properties of EMILIN1 were impaired only by enzymes able to digest gC1q and that NE is the only one among those we tested that specifically cleaves the EMILIN1 regulatory gC1q domain.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Proteases secreted by infiltrated neutrophils are able to fragment EMILIN1 in lymphoedematous tissues. This degradation is abolished by the NE specific inhibitor sivelestat but not by the MMPs broad-spectrum inhibitor GM600128. In the present study we demonstrated that the functional properties of EMILIN1 were impaired only by enzymes able to digest gC1q and that NE is the only one among those we tested that specifically cleaves the EMILIN1 regulatory gC1q domain.…”
Section: Discussionsupporting
confidence: 45%
“…EMILIN1 was fragmented in sarcomas and ovarian cancers and likely was associated to a higher proliferation rate in these tumors27. Moreover, EMILIN1 digestion by NE with the consequent weakness of the intercellular junctions of lymphatic endothelial cells was correlated to the acute phase of acquired lymphoedema28. EMILIN1 fragmentation results in a condition similar to that of the ablated molecule in Emilin1 −/− mice leading to uncontrolled cell proliferation and lymphatic phenotype121323.…”
mentioning
confidence: 99%
“…Under physiological conditions, pressure gradients induced by the ISF facilitate the uptake of fluid, macromolecules and cells into the lymphatic capillaries (Leak, 1976; Leak and Burke, 1968). The extracellular matrix glycoprotein Emilin1 is important for generation of the anchoring filaments and for proper lymphatic drainage (Danussi et al, 2008; Pivetta et al, 2016). Muscle contraction and arterial pulsation also promote the initial formation of lymph [ref].…”
Section: Role Of the Lymphatic System In Tissue Maintenancementioning
confidence: 99%
“…The absence of Emilin-1 causes a remarkable increase of active TGF- β , which consequently through the SMAD cascade upregulates genes involved in ECM destruction (MMP9) or decreases SMC proliferation (p27) [ 23 ]. The importance of Emilin-1 expression was also confirmed by the experiment of Pivetta et al [ 10 ], which showed that mice deficient in Emilin-1 had increased TGF- β activity; however, these mice had a low incidence of aneurysms and no dissection. Another study, by Lee et al [ 24 ], however, showed that embryonic mutation of the type II TGF- β receptor gene ( Tgfbr2 ) impaired elastogenesis and resulted in aneurysm formation and inflammation.…”
Section: Discussionmentioning
confidence: 74%
“…Microfibrils are composed mainly from fibrillin and several microfibril-associated proteins (elastin microfibril interface-located protein 1 (Emilin-1), microfibril-associated glycoproteins (MAGP-1,2), and fibulins) [ 9 ]. Emilin-1 is known to be a binding precursor of TGF- β , called pro-TGF- β , and inhibits its maturation by furin convertases [ 10 ]. Defects in Emilin-1 expression affect the formation and function of elastic lamellae, increasing the degree of inflammation.…”
Section: Introductionmentioning
confidence: 99%